1995
DOI: 10.1159/000264260
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age-Dependent and Sex-Related Changes of Gestational Serum Alpha-Fetoprotein

Abstract: Maternal serum alpha-fetoprotein (MSAFP) concentration values were measured in relation to maternal age and fetal sex in the 16th to 20th gestational weeks in samples taken from 9,556 pregnancies with the outcome of live, mature and healthy infants. Our results show positive significance between MSAFP concentration and maternal age (p < 0.001); we also found significantly higher AFP values in male fetuses than in female fetuses (p < 0.001). This specificity is y all probability due to the change in the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Some studies have reported that in the second trimester among pregnancies with a female fetus there is a signi®cantly lower maternal serum AFP and higher hCG level than with a male fetus (Leporrier et al, 1992;Szabo et al, 1995;Bazzett et al, 1998). That same trend is found in our ®rst trimester data.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have reported that in the second trimester among pregnancies with a female fetus there is a signi®cantly lower maternal serum AFP and higher hCG level than with a male fetus (Leporrier et al, 1992;Szabo et al, 1995;Bazzett et al, 1998). That same trend is found in our ®rst trimester data.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to differences in pregnancy-related hormones, male bearers have higher serum levels of a-fetoprotein than female bearers (13,57,58). However, (1) and (2), between bearing male offspring and ovarian cancer risk.…”
Section: Offspring Gender and Maternal Risk Of Ovarian Cancer Cancer mentioning
confidence: 99%
“…The reported [1][2][3][4] higher alphafetoprotein levels in maternal serum in pregnancies with a male fetus is probably the result of some modification of alpha-fetoprotein transfer into the maternal circulation, possibly mediated by fetal sex.…”
Section: Discussionmentioning
confidence: 95%
“…Fetal sex has been noted to affect alpha-fetoprotein concentration in maternal serum -significantly higher alpha-fetoprotein levels have been reported in pregnan cies with a male fetus [1][2][3][4], This effect, which is appar ently true in both the second and the third trimesters [2,3], is not correlated with parity, maternal age, maternal weight or weight gain or with fetal weight [3], Higher alpha-fetoprotein levels in the serum of gravi das carrying a male fetus may result either from sex-spe cific hormonal influences on transcription of the alpha- This article is also accessible online at: http:// www. karger, ch http://BioMedNct.com / karger fetoprotein gene (increased production) or from increased transfer of alpha-fetoprotein into the maternal circulation in male gestations.…”
Section: Introductionmentioning
confidence: 99%